1997
DOI: 10.1177/103841629700600102
|View full text |Cite
|
Sign up to set email alerts
|

A Whole School Approach to Career Education

Abstract: Who is responsible for career education? Why teach it anyway? This case study explores these questions as it describes a mapping process used to ascertain the extent of career education in a North Queensland school.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

1999
1999
1999
1999

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…Some form ofcareer education is occurring in most schools, whether intentionally or unintentionally. For example, Robinson (1997) found through mapping theschool curriculum that career education was occurring in many ways, even though itwas notformally included inschool documents. In addition, shesuggested thatmapping a school fostered a collaborative approach to be taken byschool staff.…”
Section: Application To Career Educationmentioning
confidence: 99%
See 2 more Smart Citations
“…Some form ofcareer education is occurring in most schools, whether intentionally or unintentionally. For example, Robinson (1997) found through mapping theschool curriculum that career education was occurring in many ways, even though itwas notformally included inschool documents. In addition, shesuggested thatmapping a school fostered a collaborative approach to be taken byschool staff.…”
Section: Application To Career Educationmentioning
confidence: 99%
“…Inaddition, school is aninfluence onthecareer development of primary and preschool age children who spend asignificant amount oftheir time in school settings. Indeed, a recent Australian study found that school isaninfluence on thecareer development ofchildren and adolescents, with orwithout the intervention ofschool staff (McMahon & Patton, 1994;1997). Betz (1993) claims that theimportance ofeducation to career development cannot beunderestimated.…”
mentioning
confidence: 99%
See 1 more Smart Citation